Phase evolution, structure, and magnetic characterization of mechanosynthesized Co40Fe30Ni30 medium-entropy alloy. (October 2019) - Jayaraman, T.V.; Rathi, A.; Thotakura, G.V.
Abstract: We demonstrate Co40 Fe30 Ni30 medium-entropy alloy is a suitable Co-rich ternary Co x Fe y Ni z ( x  ≥  y  ≥  z ) alloy precursor for designing high-entropy magnetic alloys having superior semi-hard magnetic properties. Mechanical alloying of the constituent metal powders 40 at.% Co, 30 at.% Fe, and 30 at.% Ni for 12 h resulted in a nanocrystalline Co40 Fe30 Ni30 alloy comprised of the γ phase. The alloy exhibited semi-hard magnetic behavior at ambient temperature; the intrinsic coercivity ( H CI ) and saturation magnetization ( M S ) was ~4.35 kA/m and ~141 Am 2 /kg, respectively. At sub-ambient temperatures, the alloy maintained semi-hard magnetic behavior; both H CI and M S increased by ~1.4 times and ~4%, respectively, from 300 K to 60 K. The estimated μ H (the maximum magnetic moment per atom) was ~1.51 μ B . At elevated temperatures, up to T  ≤ ~570 K, the as-prepared alloy powder maintained the γ phase, and after that α phase precipitated out. Thermal-treatment increased M S by ~13% and decreased H CI by ~31%, yet the alloy retained semi-hard magnetic behavior. At cryogenic temperatures, the thermally-treated alloy powders exhibited magnetic behavior similar to that of as-prepared alloy powder, i.e., both H CI and M S increased with the decrease in T . Grey relational analysis proposed Co40 Fe30 Ni30 as a suitable medium-entropy alloy precursor for designing novel high-entropy magnetic alloys having superior semi-hard magnetic properties. Highlights: Successfully mechanosynthesized Co40 Fe30 Ni30 medium-entropy alloy powder. Powders were micron-sized having nanocrystalline grains comprised of γ phase. As-prepared and thermally-treated powder exhibited semi-hard magnetic behavior. Co40 Fe30 Ni30 alloy is a suitable precursor for making high-entropy magnetic alloys.